The power of parks: How interracial contact in urban parks can support prejudice reduction, interracial trust, and civic engagement for social justice. (December 2022) - Powers, Sammie L.; Webster, Nicole; Agans, Jennifer P.; Graefe, Alan R.; Mowen, Andrew J.
Abstract: Urban parks have long been discussed as spaces of diversity and democracy with the potential to foster intergroup contact among racially and ethnically diverse visitors, but the outcomes of contact in parks are less well understood. This survey of racially and ethnically diverse U.S. urban residents investigated the relationships between interracial contact in urban parks, prejudice, interracial trust, critical consciousness, social justice civic attitudes, and social justice civic behaviors ( n  = 931). Results demonstrated that more frequent and positive interracial contact in urban parks was associated with lower levels of prejudice, higher levels of interracial trust, higher levels of critical consciousness, stronger social justice civic attitudes, and greater engagement in social justice civic behaviors, with many of these relationships robust in comparisons across racial and ethnic groups. Park agencies, community organizations, and supporting foundations seeking to stimulate interracial contact with these factors in mind should focus on creating environments conducive to frequent, positive contact through providing safe and welcoming parks with diverse features/amenities and advancing equitable and inclusive engagement, representation, and resource allocation. Highlights: Urban parks are a valuable context to stimulate positive interracial contact. Positive park interracial contact supports favorable outcomes for diverse visitors. Positive park contact is associated with lower prejudice and higher interracial trust. Positive interracial contact in parks supports critical consciousness development. Positive park interracial contact supports civic engagement for social justice.